2012
DOI: 10.1039/c2nr31449e
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of red-emitting lysozyme-stabilized Ag nanoclusters

Abstract: A facile approach was developed to prepare positively charged and red-emitting lysozyme-stabilized Ag nanoclusters (Lys-AgNCs) using NaBH₄ as a reducing agent at room temperature. The Lys-AgNCs can be applied in the highly selective detection of Hg²⁺.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 40 publications
(40 reference statements)
3
95
0
1
Order By: Relevance
“…3F, two peaks at 368.2 eV and 374.2 eV were observed in the Ag 3d XPS spectra of (AgNP@Lys/TA) 10 and (AgNP@Lys/TA) 10.5 nanobrous mats corresponding to Ag 3d 5/2 and Ag 3d 3/2 , respectively. These results are in good agreement with the results of Zhou et al 19 The presence of signal at 368.2 eV revealed that Ag + exist in the complex. 34 The Moreover, with the increase of particle size, the binding energy would have a slight blue shi to about 367.7 eV.…”
Section: Surface Composition Analysis Of Agnp-lys/ta Nanobrous Matssupporting
confidence: 95%
“…3F, two peaks at 368.2 eV and 374.2 eV were observed in the Ag 3d XPS spectra of (AgNP@Lys/TA) 10 and (AgNP@Lys/TA) 10.5 nanobrous mats corresponding to Ag 3d 5/2 and Ag 3d 3/2 , respectively. These results are in good agreement with the results of Zhou et al 19 The presence of signal at 368.2 eV revealed that Ag + exist in the complex. 34 The Moreover, with the increase of particle size, the binding energy would have a slight blue shi to about 367.7 eV.…”
Section: Surface Composition Analysis Of Agnp-lys/ta Nanobrous Matssupporting
confidence: 95%
“…13 Dendrimers, synthetic polymers, biopolymers, thiol ligands, and inorganic matrices have been used as the stabilizing ligands for AgNCs. 6,11,[14][15][16][17] In 2004, Dickson and coworkers first discovered the formation of DNA-templated Ag nanoclusters (DNA-AgNCs) where they showed that DNA acts as a template for the time-dependent and size-specific formation of nanoclusters. 18 Since then, DNA-AgNCs have become a research field of growing interest.…”
Section: Introductionmentioning
confidence: 99%
“…The three silver nanoclusters capped with denatured lysozyme (dLys-AgNCs) were prepared according to the report by Chen et al 28 with some modification. The reactant molar ratio of AgNO 3 to lysozyme was 1:1, 2:1 and 4:1 for synthesizing dLys-AgNCs 1, dLys-AgNCs 2 and dLys-AgNCs 3, respectively.…”
Section: Preparation Of Dlys-agncsmentioning
confidence: 99%
“…Later, some other proteins, like lysozyme 32 , insulin 33 , pepsin 34 , trypsin 35 , as well as horseradish peroxidase 36 and lactotransferrin 37 were also applied as scaffold for the synthesis of metal nanoclusters. The four disulfide bonds in the secondary structure of lysozyme were broken in alkaline conditions during synthesis, and could provide binding sites for Ag nanoclusters and stabilize the nanoclusters 28 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation